The Cortes of Castile-León, 1188-1350 - O'Callaghan, Joseph F. (The Middle Ages Series, 2017)
Like the English parliament, the French Estates, and the German imperial diet, the cortes of medieval Castile and Leon is an example of development of the parliamentary system.